Developing Bilingual E-Comics (Aceh–Indonesian) on Tajwid Rules to Enhance Learning Outcomes in Madrasah - Cut Dewi Rahma; Zulfatmi Zulfatmi; Hayati Hayati; Realita Nurdin; Salma Hayati; Sulhan Yus (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2026)
The use of innovative learning media is now an urgent need to address increasingly complex learning challenges, especially in strengthening students' understanding and interest in learning.This study aims to develop innovative learning media in the form of bilingual e-comics (Aceh–Indonesian) on tajwid material, specifically the rules of Noon sakinah or tanween in Min. The background of this study is based on the low effectiveness of tajwid learning due to the dominance of conventional methods, the lack of interactive media, and the language gap between the lesson material and the daily lives of students in Aceh. Through the 4D (define, design, develop, disseminate) Research and Development (R&D) approach, this research focuses on the stages of needs analysis and product design by involving Qur'an Hadith teachers from various Madrasah Ibtidaiyah Negeri (State Elementary Islamic School) in Aceh. The survey results show that all teachers recognize the importance of learning media and the majority are in dire need of innovative media such as bilingual e-comics. The design process was carried out by compiling tajwid material in a bilingual digital comic format, complete with contextual illustrations and narratives that are close to the local culture. Expert validation stated that this media product was feasible with minor revisions, and the teachers' responses were very positive in terms of ease of use and attractiveness in the classroom. Limited implementation at Madrasah Ibtidaiyah Negeri 11 Banda Aceh showed a significant increase in student understanding and motivation. This study recommends the use of bilingual e-comics as a modern solution to overcome tajwid learning challenges, while also serving as an effort to preserve local culture through the integration of local languages in digital learning materials.